Implementation of Eastern Culture (Indonesia) About the Influence of Globalization on Social Studies Education Students of FKIP Lambung Mangkurat University in Belawang Village, Belawang District, Barito Kuala Regency - Triyono, Sigit; Syaharuddin, Syaharuddin; Handy, Muhammad Rezky Noor; Syarifuddin, Syarifuddin; Rusmaniah, Rusmaniah; Winata, Atikah (Universitas Lambung Mangkurat, 2024)
This article aims to describe the implementation of eastern (Indonesian) culture regarding the influence of globalization on students of Social Sciences Education FKIP Lambug Mangkurat University in Belawang Village, Belawang District, Barito Kuala Regency. The method used in this article is community service activities carried out on 07-10 August 2023 in Belawang Village, Belawang sub-district, Barito Kuala Regency, then using 1) problem discovery observation stages, planning stages and implementation stages; 2) presenting data in descriptive form; and 3) drawing conclusions based on activities so as to describe the research results systematically. In the results analysis section, the author uses safety engineering studies after fire incidents, apart from that, it is also supported by the results of interviews with victims of fire disasters. Service activities are carried out with two activities, namely Raising Funds from the academic community (lecturers, students and the community)